185k views
1 vote
if you were using the subsitution method to solve the following system, write the new equation after the expression equivalent to x from the first equation is subsituted into the second equation x+3y=8 2x-y=2

1 Answer

3 votes
To use substitution, you find the part of the first equation that is equal to x, and substitute it for x into the second equation, then you can solve for y as it is the only variable. In the first equation x is equal to 8-3y. If we substitute this into the second equation we get 2(8-3y)-y=2. We then multiply this out to get 16-6y-y=2, or 16-7y=2.
User Manoj Agarwal
by
6.5k points